Evolution of agricultural mechanization in Kenya - De Groote, Hugo; Marangu, Cliff; Gitonga, Zachary M. (International Food Policy Research Institute, 2020)
Agricultural intensification is key to feed the rapidly increasing African population. Although the use of improved varieties has increased substantially over the last 20 years, the use of land- and labor-saving technologies, such as mechanization, has lagged behind. This study reviews existing literature and uses four household surveys conducted between 1992 and 2012 to analyze the evolution of agricultural mechanization in Kenya. The results show persistently low levels of mechanization in Kenya; in 2012, most farm households still used only hand tools. More than a quarter of farmers (28 percent) had a plow, but very few (2 percent) had a tractor. From 1992 to 2012, the percentage of farmers with oxen increased from 17 percent to 33 percent, but those with tractors decreased from 5 percent to 2 percent. Tractors were most important in the highlands, whereas animal traction was most important in the dry areas and moist mid-altitude zone. Adoption of tractors increased with income, acreage, and age. Adoption of animal traction increased with absentee husbands, age, sales of maize, livestock, family size, and access to extension; it decreased with land, fertilizer use, and income. Mechanization in Kenya is likely to continue to depend on animal traction, which is not linked to farm size, complements labor, helps to reduce fertilizer use, increases commercial maize production, and has room to grow—particularly in the highlands. Agricultural extension, development projects, and research should consider the opportunities in animal traction and provide training and research on appropriate technologies in areas with sufficient land area.